A EQUOTERAPIA NA REABILITAÇÃO DE CRIANÇAS PORTADORAS DE PARALISIA CEREBRAL - Araujo, Ana Eugenia Ribeiro de Araujo e (2007)
Cerebral Paralysis (CP) comprehends a series of non progressive syndromes of motor and posture disturbances, resulting from irreversible damage to the developing central nervous system. The hippotherapy is a therapeutical and educational method that uses a horse in an interdisciplinary approach attempting to enhance the posture stability in children affected by Cerebral Paralysis (CP). This work aim is to evaluate the benefits PC diagnosed children can attain after one year participation in an hippotherapy program. 27 spastic diplegia PC diagnosed children were studied (15 boys and 17 girls) ranging from 2 to 12 years of age. As to evaluate the following body parts: head and neck, shoulders and scapulae, trunk, vertebral column and pelvis, before and after hippotherapy treatment, a scale, standardized by the interdisciplinary medical team of the hippotherapy center, was used. The program was conducted once a week, in sessions of 45 minutes each. There were verified posture benefits statistically significant (p<0.05) in all body parts, especially in those presenting the worst asymmetry conditions before the treatment, such as the trunk and pelvis. One can conclude stating that the hippotherapy treatment positively influenced the posture adjustment as well as the children s static and dynamic equilibrium, thus improving their motor abilities and contributing to the walking prediction.